Impact of Human Resources Development on Organizational Financial Performance and Its Impact on Good Government Governance - Safkaur, Otniel; Sagrim, Yohanis (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to determine the effect of Human Resources Development on Financial Performance and Its Implication on Good Government Governance. Accounting is concerned in recording financial reporting to the management of the company as a business entity that is not the owner of the company so that the concept of business unity is the center of accountability and financial statements are central to the company's financial accountability to be good. In Government Accounting Standards (SAP) are standardized and confirmed the existence of Reporting Entities and Accounting Entities, as Reporting Entities is a government unit consisting of one or more accounting entities which according to statutory provisions must submit accountability reports in the form of financial and non-financial reports. Financial reporting is conveyed internally and tiered to higher units in the context of consolidating financial statements by financial reporting entities. Each government unit can be determined as an accounting entity if the unit in question manages the company's financial budget. Keywords: Human Resources Development, Financial Performance, Good Government Governance JEL Classifications: G2, O15, O16 DOI: https://doi.org/10.32479/ijefi.8508